Association between blood chromium and hepatic steatosis assessed by liver ultrasound transient elastography: National Health and Nutrition Examination Survey 2017–2020 - Xiang, Yingying; Zhou, Ruonan; Wang, Ziwei; Xue, Yingying; Cao, Yue; Shen, Lixuan; Zhu, Ziwei; Xu, Pingyuan; Zhou, Guowei; Shang, Wenbin (Frontiers in Nutrition, 2024)
Background Hepatic steatosis is a significant pathological feature of fatty liver disease (FLD) which is widely spread with no effective treatment available. Previous studies suggest that chromium (Cr) intake reduces lipid deposition in the liver in animals. However, the connection between blood Cr and hepatic steatosis among humans remains inconclusive. Methods Using the data from the National Health and Nutrition Examination Survey (NHANES) 2017–2020, we performed a cross-sectional analysis, including 4,926 participants. The controlled attenuation parameter (CAP) measured by the vibration controlled transient elastography (VCTE) was used to evaluate the degree of liver steatosis. Weighted univariate regression, multivariate linear regression, smooth fitting curves and subgroup analysis were used. In addition, we carried out trend tests, multiple interpolations, and interaction analyses to conduct sensitivity analyses. Results After adjusting with various covariables, multivariate linear regression analysis demonstrated a significant negative correlation between blood Cr and CAP [β (95% CI) = −5.62 (−11.02, −0.21)]. The negative correlation between blood Cr and CAP was more significant in the males, 50–59 years, overweight, hypercholesterolemia, HDL-C ≥ 65 mg/dL, HbA1c (5.70–6.10 %), HOMA-IR (0.12–2.76), total bilirubin (0.30–0.40 mg/dL), ever alcohol consumption subjects. Of note, the relationships between blood Cr and CAP followed a U-shaped curve in the smokers and non-smokers, with blood Cr thresholds of 0.48, 0.69 μg/L, respectively. Conclusions There is an independently negative correlation between blood Cr and hepatic steatosis in American. Our study provides clinical researchers with a new insight into the prospective prevention of hepatic steatosis.